The Determinants of Carbon Emission Disclosure Moderated by Institutional Ownership - Krisnawanto, Kurniawan; Solikhah, Badingatus (Accounting Analysis Journal, 2019)
The purpose of this study is to analyze the influence of company size, profitability, environmental performance, media exposure to carbon emission disclosure and institutional ownership as a moderating variable. The population in this study was all companies which published sustainability reports and were listed on the Indonesia Stock Exchange in 2014-2018 with a total of 43 companies. The sample in this study was included as saturated samples so that the total sample was 43 companies with 132 units of analysis. The data analysis techniques used were descriptive statistical analysis and inferential statistical analysis in Eviews9. The results show that environmental performance has a significant positive effect on carbon emission disclosure. Meanwhile, company size, profitability, and media exposure do not affect on carbon emission disclosure. Then, institutional ownership weakens the effect of environmental performance on carbon emission disclosure. Institutional ownership also cannot moderate the effect of company size, profitability, and media exposure on carbon emission disclosure. Based on the results of the study, it can be concluded that the factor that is proven to affect carbon emission disclosure is environmental performance. Further researchers are advised to use other measuring devices so that they can get results from other perspectives.